SISTEM INFORMASI PENJUALAN TIKET BOAT BERBASIS WEB - Hadijah, Siti; Usman; Yunita, Fitri (JURNAL PERANGKAT LUNAK, 2020)
ABSTRACT This system provides speed boat ticket booking services online. This system helps prospective passengers when they want to depart with different specific destinations. This system is only implemented in three speed boat counters and these three boat counters have not used the online ticket booking system, for booking activities can only be done via telephone or come directly to the pocket. Sometimes when ordering tickets customers often run out of seats, then when making reports employees require a relatively long time because they have to calculate all transactions using a calculator so that it can cause errors during the addition process. It is hoped that through this information system prospective passengers can immediately order boat tickets that still provide empty seats, find out departures, schedules, costs and destinations that can be done online. This system is not only useful for prospective passengers, but this system can be useful for ticket holders and employees. With this system employees can also be facilitated when they want to make transaction reports, find out all information about passengers. The owner can also immediately know the total transactions per day, without having to wait for monthly reports. In designing this web-based boat ticket ordering information system, it is drawn into the form of a DFD (Data Flow Diagram) diagram, while the test used is UAT (User Acceptance Test) and using the PHP (Personal Home Page) programming language.